The Effect of Inclusive School Climate on Job Burnout Among Elementary School Inclusive Teachers: The Mediating Role of Teaching Efficacy Under the Ecosystem Theory - Yue Yang; Dan Zhou (Education Sciences)
Grounded in the Job Demands–Resources framework, this mixed-methods study seeks to (a) quantify the directional relationships between school inclusive climate, job burnout, and teaching efficacy, and (b) identify mediating mechanisms to inform targeted interventions in inclusive education settings. Study I employed the School Inclusive Climate Scale, Job Burnout Scale, and Teachers’ Teaching Efficacy Scale to assess 613 primary and secondary school teachers involved in inclusive education. Study II conducted semi-structured interviews. School inclusive climate showed significant negative correlations with job burnout and positive correlations with teaching efficacy. A negative correlation was also observed between job burnout and teaching efficacy. Mediation analyses revealed that teaching efficacy partially mediated the relationship between school inclusive climate and job burnout, explaining 50% of the total effect. The qualitative interview findings corroborated and complemented the quantitative questionnaire results. School inclusive climate demonstrates both direct effects on job burnout and indirect effects mediated by teachers’ teaching efficacy.